2021
DOI: 10.13005/bpj/2189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Herbal Preparation "Licorice Oil" on the State of Hematopoiesis in Rats Under Ionizing Irradiation

Abstract: The radioprotective effect of the herbal preparation "Licorice oil" on the hematopoietic system and oxidative stress was studied. The experiment was carried out on 30 male Wistar rats, divided into 3 groups. The first group is control group, the second is irradiation with 6Gy, third group - a week before irradiation and two weeks after, received "Licorice oil" intragastrically at a dose of 2.5 ml/kg of body weight. Gamma irradiation significantly reduced the number of erythrocytes, hemoglobin, hematocrit, leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Results of this study revealed that, pre-treated by licorice extract can mitigate all the adverse effects of cisplatin on hematological parameters. (Iztleuov et al, 2021) also obtained similar results that rats were intoxicated by Gamma irradiation the emptying of the bone marrow, which is defined by a decrease in the level of cellular elements in the blood and bone marrow cellularity by 41%, 50%, and 25%, led to a noticeable and lasting shift in the peripheral blood picture. In comparison to the control group, 42 percent, 35 percent, and 46 percent improved.…”
Section: Discussionsupporting
confidence: 59%
“…Results of this study revealed that, pre-treated by licorice extract can mitigate all the adverse effects of cisplatin on hematological parameters. (Iztleuov et al, 2021) also obtained similar results that rats were intoxicated by Gamma irradiation the emptying of the bone marrow, which is defined by a decrease in the level of cellular elements in the blood and bone marrow cellularity by 41%, 50%, and 25%, led to a noticeable and lasting shift in the peripheral blood picture. In comparison to the control group, 42 percent, 35 percent, and 46 percent improved.…”
Section: Discussionsupporting
confidence: 59%